2014
DOI: 10.1021/cg5005837
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Various Guests by an Anionic In-Metal–Organic Framework Containing Tritopic BTB Ligand: Crystal Structure of Reichardt’s Dye Captured in an In-Metal–Organic Framework

Abstract: The reaction between 1,3,5-benzenetribenzoic acid (H 3 BTB) and In(NO 3 ) 3 hydrate in diethylformamide yielded a new In III -metal-organic framework, [(CH 3 CH 2 ) 2 NH 2 ] 3 [In 3 (BTB) 4 ]•10DEF•14H 2 O (I). The countercation and solvent-free doubly interpenetrated I potentially contains 71.0% of solvent accessible void. Although the framework of I was not stable enough to maintain its original structure when the solvent molecules were removed, the as-prepared I was found to be a very good sorbent for acri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Additionally, there should be a counter-cation near each [In(O 2 CR) 4 ] − node because of charge matching. There are many examples of 3D In-MOFs solely derived from ditopic, tritopic, tetratopic, and pentatopic carboxylate-based bridging ligands (Sun et al, 2002;Lin et al, 2007Lin et al, , 2012Huh et al, 2009;Gu et al, 2012;Yu et al, 2012;Zheng et al, 2013;Cho et al, 2014;Huang et al, 2014;Johnson et al, 2014;Wang et al, 2014;Grigoropoulos et al, 2016;Li et al, 2016;Aguirre-Díaz et al, 2017;Zhao et al, 2017;Yang et al, 2019). The most common counter-cations are either Me 2 NH + 2 or Et 2 NH + 2 which can be in-situ generated from the solvents: N,Ndimethylformamide (DMF) or N,N-diethylformamide (DEF).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there should be a counter-cation near each [In(O 2 CR) 4 ] − node because of charge matching. There are many examples of 3D In-MOFs solely derived from ditopic, tritopic, tetratopic, and pentatopic carboxylate-based bridging ligands (Sun et al, 2002;Lin et al, 2007Lin et al, , 2012Huh et al, 2009;Gu et al, 2012;Yu et al, 2012;Zheng et al, 2013;Cho et al, 2014;Huang et al, 2014;Johnson et al, 2014;Wang et al, 2014;Grigoropoulos et al, 2016;Li et al, 2016;Aguirre-Díaz et al, 2017;Zhao et al, 2017;Yang et al, 2019). The most common counter-cations are either Me 2 NH + 2 or Et 2 NH + 2 which can be in-situ generated from the solvents: N,Ndimethylformamide (DMF) or N,N-diethylformamide (DEF).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the spatial positioning of dye molecules inside pre-organized channels of MOFs is an ideal method to investigate the structure-dependent optical properties of dyes. For example, we recently demonstrated that large RD was effectively encapsulated in mesoscale channels of anionic In-BTB, [Et 2 NH 2 ] 3 [In 3 (BTB) 4 ], through a cation-exchange process 22 . The anionic framework of In-BTB is an especially good host for RD cations despite its large molecular dimensions compared to small neutral acridine orange (AO).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, In-BTB containing RD, RD@In-BTB, exhibited distinct visible absorption properties compared to non-encapsulated free RD based on solid-state UV/Vis absorption spectroscopy. To elucidate these different optical properties, the crystal structure of RD@In-BTB was successfully refined for the first time 22 . The structural comparison of the encapsulated RD and the free RD crystal grown in solution showed large distortion of the main molecular axis of RD in RD@In-BTB.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,5‐Tri(4‐carboxyl phenyl) benzene (H 3 BTB) has three carboxyl groups in its molecular structure which is a potential B 3 monomer to construct hyperbranched polymers. Although until now, H 3 BTB is widely used to synthesize porous coordination polymers . To the best of the author's knowledge, there have no report concerning the synthesis of hyperbranched polymers using H 3 BTB as a reactive monomer.…”
Section: Introductionmentioning
confidence: 99%